2020
DOI: 10.13075/ijomeh.1896.01460
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tobacco smoking on dental periapical condition in a sample of an adult population of the Łódź region, Poland

Abstract: Objectives: Epidemiological studies show that apical periodontitis (AP), alongside tooth decay, is the most common oral disease. The aim of the study was to evaluate the influence of smoking on the prevalence of AP in the population of the Łódź region, Poland. Material and Methods: The study involved 815 first-time, randomly selected patients reporting to the Central Teaching Hospital of the Medical University of Lodz. The studied group was a systematic sample of the population admitted for treatment in 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Regarding the possible influence of smoking in the outcome of RCT, several cross‐sectional studies have not found an association between smoking and the presence of RPL in RFT (Marending et al, 2005; Segura‐Egea et al, 2008, 2011; Sopińska & Bołtacz‐Rzepkowska, 2020; Table 2, top). On the contrary, the study of Jansson (2015) reported a significant correlation between smoking and the prevalence of RFT with AP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the possible influence of smoking in the outcome of RCT, several cross‐sectional studies have not found an association between smoking and the presence of RPL in RFT (Marending et al, 2005; Segura‐Egea et al, 2008, 2011; Sopińska & Bołtacz‐Rzepkowska, 2020; Table 2, top). On the contrary, the study of Jansson (2015) reported a significant correlation between smoking and the prevalence of RFT with AP.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review concluded that smokers have a prevalence of AP and RCT that is greater than 2.5 times higher than nonsmokers (Pinto et al, 2020). Several studies have also found that smoking is associated with higher prevalence of RCT (Segura-Egea et al, 2008, 2011Sopińska & Bołtacz-Rzepkowska, 2020). RCT has been shown to be almost two times more prevalent in smokers, with a dose-response relationship (Krall et al, 2006).…”
Section: Smoking Habitsmentioning
confidence: 99%
“…Four studies were finally included in the analysis: (1) Segura-Egea et al (2008) [24]; (2) Segura-Egea et al (2011) [51]; (3) Jansson (2015) [52]; (4) Sopi ńska and Bołtacz-Rzepkowska (2020) [53]. Study design, study sample, diagnosis of RPL, main results, and evidence level are summarized in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, the recent study conducted by Sopi ńska and Bołtacz-Rzepkowska [53] aimed to evaluate the influence of smoking on the prevalence of AP in the population of the Łódź region, Poland. Results show no difference in the frequency of RFT with AP between smokers (37.6%) and control subjects (35.8%) (OR = 1.08; 95% CI = 0.88-1.33; p = 0.451).…”
Section: Interpretation and Assessment Of The Included Studiesmentioning
confidence: 99%
“…The OPG was used to show all teeth in a single x-ray, easy of using OPG, in addition to decreasing the lost time of x-ray taken by intraoral periapical x-ray (PA x-ray) films to achieve complete mouth radiography (we need approximately 14 periapical x-rays at minimum to show all teeth while single OPG can give accepted information about RCT teeth). 23,24 Viewing the radiography was standardized as all films were examined in a unified level of indoor-illumination/light intensity (darkened room), radiographs were shown on a computer screen in which the light could be controlled using "Carestream R " software for the best possible contrast.…”
Section: Presence Of Rct Teethmentioning
confidence: 99%